Attempts of Lithuanian State Archive Institutions to Search for Archived Heritage Exported from Lithuania in the Past or Related to Lithuania - Lukšaitė, Daiva (Knygotyra, 2022)
As archival institutions are operating under the conditions of globalization, digital culture, and technological changes, displaced archives are evaluated from various aspects (theoretical, sociopolitical, or technological). Ensuring the accessibility of displaced archives remains the fundamental goal of archives, which is inseparable from the strategies of document heritage accumulation (acquisition) in archives, the application of archival principles or document concepts, knowledge of the history of a country or a specific region, and knowledge of the legal system. The research and good practice of displaced archives is also of importance for the state archives of Lithuania. Professor Zigmantas Kiaupa discussed the efforts by archives in an attempt to recover documents illegally exported from Lithuania. However, searches for the archival heritage by the Lithuanian state archives after 1990 have not become the object of scientific publications. The article gives a review of the actions of the state archives system since 1990 which was aimed at identifying the documentary heritage related to Lithuania but preserved abroad. The focus of attention is on the creation of legal regulation, accumulation of documents, and information about the identified documents related to Lithuania and the further activities of state archives. Archival sources show that, since 1990, the identification of documents related to Lithuania and preserved abroad along with the activity of their storage in Lithuania is a continuous and consistent process, although the scope of this activity is not large, and only a few archives have been participating in its implementation. The review of the activity of the Office of the Chief Archivist of Lithuania and the state archives proves that international agreements or agreements of cooperation between two countries contribute to the establishment of close professional relationships, but it is not a prerequisite for the document search. It is more important to provide methodological assistance to those who have preserved the documents related to Lithuania (especially to Lithuanians living abroad) as well as to coordinate the activities related to document management, their description, digitization, and publication, as these activities require different competencies. The article concludes that the legislative regulation of Lithuania created legal opportunities for the state archives to make independent decisions regarding the strategy of collecting documents related to Lithuania and to be more actively involved in the activities of digital cultural heritage actualization. The state archives of Lithuania do not associate the accumulation of documentary heritage related to Lithuania only with the physical form of documents. The article argues that the accumulation of digital cultural objects and the dissemination of descriptive information in archives using several information retrieval tools further complicates the accessibility of information. This is why the accumulation of information and its provision to the user, based on the one-stop-shop principle, should be regarded as a priority.